Diketopyrrolopyrrole (DPP)-Based Materials and Its Applications: A Review - Bao, Wei Wei; Li, Rui; Dai, Zhi Cheng; Tang, Jian; Shi, Xin; Geng, Jie Ting; Deng, Zhi Feng; Hua, Jing (Frontiers in Chemistry, 2020)
Diketopyrrolopyrrole (DPP) and its derivatives have been widely studied in the past few years due to its intrinsic physical and chemical properties, such as strong electron-withdrawing, deep color, high charge carrier mobility, strong aggregation, good thermal-/photo-stability. In the 1970s, DPP was developed and used only in inks, paints and plastics. Later, the DPP containing materials were found to be potential in other applications, typically in electronic device, which had attracted lots of attention by the scientists. In this feature article, the synthesis pathway regarding to DPP-based materials and their applications in organic field-effect transistors, photovoltaic device, sensors, two photo-absorption materials and others have been reviewed. In addition, a future-outlook is pointed out. The final goal of this review is to outline a theoretical scaffold for the development of conjugated DPP-based materials, which is potential for its multi-applications.